TINGKAT KEBUGARAN WANITA PREMENOPAUSE DI KELURAHAN SUKAJAYA KOTA PALEMBANG - M. Kus Fitriani Fruitasari; Anjelina Puspita Sari (JURNAL KESEHATAN INDRA HUSADA, 2022)
Background: Every woman will enter menopause. Before menopause occurs, physiologically a woman's body will transition to prepare for menopause. This transition period is called premenopause. During this transition period, there are fluctuations in female hormones and the level of fitness will decrease. The decline in fitness levels greatly affects the quality of life of premenopausal women. This study aims to describe the physical fitness of women who enter the premenopause period in Sukajaya Village, Palembang City. Methods: This research design uses a descriptive method with a quantitative approach that provides an overview of the fitness level of women entering the premenopausal period in Sukajaya Village, Palembang City. Methods: This research design uses a descriptive method with a quantitative approach that provides an overview of the fitness level of women entering the premenopausal period in Sukajaya Village, Palembang City. Conclusion: The fitness level of premenopausal women in Kelurahan Sukajaya in the category of average, above average, below average, poor and very bad. There are no premenopausal women who are in the category above average and perfect.)